Physico Chemical Analysis and HPTLC Evaluation of Kokilakshadi Kwatha Churna (International Journal of Ayurveda and Pharma Research, 2022)
Kokilakshadi Kashaya mentioned in Bhaishajya Ratnavali, Vataraktadhikara, it is a therapeutic formulation to treat Vatarakta. It is also used by Ayurvedic practitioners for treating hyperuricemia. The symptoms of hyperuricemia and gouty arthritis are similar to Vatarakta, a disease explained in classical Ayurvedic textbooks. Kokilakshadikwatha contains Kokilaksha and Guduchi and Pippalichurna given as Anupana of this formulation Physico chemical analysis of individual drug and formulation with modern parameters increase their scope and acceptance. The study was based on standard analytical parameters proposed by API. Method: Kokilakshadi Kwatha powder was evaluated for physico chemical analysis and phyto chemical screening. The analysis was done by using the parameters like Organoleptic features, loss on drying, acid soluble extractive, water soluble extractive. Results: Analytical parameters of individual drugs were done. All analytical parameter were within limit. Analytical parameter of Kokilakshadi Kwatha Churna like loss on drying 10.4%w/w, acid insoluble ash 0.79%, alcohol soluble extractive 11.2%w/w, water soluble extractive 7.8%w/w, pH 5.78 were obtained. High Performance Thin Layer Chromatography (HPTLC) profile of Kokilakshadikwatha powder showed 13 peaks at 254nm and 14 peaks at 366nm. Preliminary phytochemical screening test revealed the presence of steroids, alkaloids, phenols, flavonoids. Conclusion: The obtained data can be used for future comparative references